IR/IGF1R signaling as potential target for treatment of high-grade osteosarcoma. - Kuijjer, M; Peterse, E; van den Akker, B; Briaire-de Bruijn, I; Serra, M; Meza-Zepeda, L; Myklebost, O; Hassan, A; Hogendoorn, P; Cleton-Jansen, A (BioMed Central, 2013)
Background: High-grade osteosarcoma is an aggressive tumor most often developing in the long bones of adolescents, with a second peak in the 5th decade of life. Better knowledge on cellular signaling in this tumor may identify new possibilities for targeted treatment. Methods: We performed gene set analysis on previously published genome-wide gene expression data of osteosarcoma cell lines (n=19) and pretreatment biopsies (n=84). We characterized overexpression of the insulin-like growth factor receptor (IGF1R) signaling pathways in human osteosarcoma as compared with osteoblasts and with the hypothesized progenitor cells of osteosarcoma – mesenchymal stem cells. This pathway plays a key role in the growth and development of bone. Since most profound differences in mRNA expression were found at and upstream of the receptor of this pathway, we set out to inhibit IR/IGF1R using OSI-906, a dual inhibitor for IR/IGF1R, on four osteosarcoma cell lines. Inhibitory effects of this drug were measured by Western blotting and cell proliferation assays. Results: OSI-906 had a strong inhibitory effect on proliferation of 3 of 4 osteosarcoma cell lines, with IC50s below 100 nM at 72 hrs of treatment. Phosphorylation of IRS-1, a direct downstream target of IGF1R signaling, was inhibited in the responsive osteosarcoma cell lines. Conclusions: This study provides an in vitro rationale for using IR/IGF1R inhibitors in preclinical studies of osteosarcoma.